Murine model of elastase-induced proximal thoracic aortic aneurysm through a midline incision in the anterior neck - Deng, Jianqing; Li, Dandan; Zhang, Xuelin; Lu, Weihang; Rong, Dan; Wang, Xinhao; Sun, Guoyi; Jia, Senhao; Zhang, Hongpeng; Jia, Xin; Guo, Wei (Frontiers in Cardiovascular Medicine, 2023)
Objective This study was performed to develop a murine model of elastase-induced proximal thoracic aortic aneurysms (PTAAs). Methods The ascending thoracic aorta and aortic arch of adult C57BL/6J male mice were exposed through a midline incision in the anterior neck, followed by peri-adventitial elastase or saline application. The maximal ascending thoracic aorta diameter was measured with high-resolution micro-ultrasound. Twenty-eight days after the operation, the aortas were harvested and analyzed by histopathological examination and qualitative polymerase chain reaction to determine the basic characteristics of the aneurysmal lesions. Results Fourteen days after the operation, the dilation rate (mean ± standard error) in the 10-min elastase application group (n = 10, 71.44 ± 10.45%) or 5-min application group (n = 9, 42.67 ± 3.72%) were significantly higher than that in the saline application group (n = 9, 7.37 ± 0.94%, P < 0.001 for both). Histopathological examination revealed aortic wall thickening, degradation of elastin fibers, loss of smooth muscle cells, more vasa vasorum, enhanced extracellular matrix degradation, augmented collagen synthesis, upregulated apoptosis and proliferation capacity of smooth muscle cells, and increased macrophages and CD4+ T cells infiltration in the PTAA lesions. Qualitative analyses indicated higher expression of the proinflammatory markers, matrix metalloproteinase-2 and -9 as well as Collagen III, Collagen I in the PTAAs than in the controls. Conclusion We established a novel in vivo mouse model of PTAAs through a midline incision in the anterior neck by peri-adventitial application of elastase. This model may facilitate research into the pathogenesis of PTAA formation and the treatment strategy for this devastating disease.